2015
DOI: 10.1002/net.21589
|View full text |Cite
|
Sign up to set email alerts
|

The school bus routing and scheduling problem with transfers

Abstract: In this article, we study the school bus routing and scheduling problem with transfers arising in the field of nonperiodic public transportation systems. It deals with the transportation of pupils from home to their school in the morning taking the possibility that pupils may change buses into account. Allowing transfers has several consequences. On the one hand, it allows more flexibility in the bus network structure and can, therefore, help to reduce operating costs. On the other hand, transfers have an impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“…The more students join in one area or destination, the more expensive the cost will be. Conversely, if in an area or the goal is the number of students is small, then the cost will Advances in Social Science, Education and Humanities Research, volume 382 be more expensive [13]. Some strategies carried out by the association as managers of school transportation by determining the type of vehicle used.…”
Section: Determination Of School Transportation Costsmentioning
confidence: 99%
“…The more students join in one area or destination, the more expensive the cost will be. Conversely, if in an area or the goal is the number of students is small, then the cost will Advances in Social Science, Education and Humanities Research, volume 382 be more expensive [13]. Some strategies carried out by the association as managers of school transportation by determining the type of vehicle used.…”
Section: Determination Of School Transportation Costsmentioning
confidence: 99%
“…In one season alone, one study found that 23% of elite level Rugby Union participants suffered a concussion (Shuttleworth-Edwards et al, 2008). It is well understood that both correct tackler and ball carrier technique are necessary for successful and safe participation in rugby union (Hendricks & Lambert, 2010Tierney, Denvir, Farrell, & Simms, 2018a, 2018cTierney, Krosshaug, Wilson, & Simms, 2015), and that incorrect tackle technique is a risk factor for injury Hendricks et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Rather interesting is the work of , in which transfer points and tree‐structures of solutions are considered. In more detail, the authors study the effect of those transfer points on the solution quality (costs).…”
Section: Problem Description and Related Workmentioning
confidence: 99%